2020
DOI: 10.1002/jhbp.771
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic artery thrombosis following living donor liver transplantation: A 14‐year experience at a single center

Abstract: BackgroundHepatic artery thrombosis (HAT) following liver transplantation is a serious complication that may lead to graft loss and ultimately death. Retransplantation and surgical recanalization for HAT have traditionally been the predominant methods of treatment. However, with the development of endovascular therapies, including percutaneous transluminal angioplasty, thrombolysis, and stent insertion, these methods are now mainly used because they allow prompt management.MethodsFrom January 2005 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…The authors suggested that endovascular therapy could be an alternative therapeutic option for HA occlusion in the first 24 hrs post-transplant. Our findings also agree with Park et al [26] who reported successful endovascular therapy in 10/13 cases of e-HAT in the first 48hrs post-LDLT, where bleeding occurred in 2/13 cases, prompting endovascular embolization in one patient & laparotomy in the other. Finally, it is worth pointing out that in our LDLT experience, with time, we gradually implemented some additional technical precautions, aiming to minimize the potential risks of endovascular therapy as much as possible.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The authors suggested that endovascular therapy could be an alternative therapeutic option for HA occlusion in the first 24 hrs post-transplant. Our findings also agree with Park et al [26] who reported successful endovascular therapy in 10/13 cases of e-HAT in the first 48hrs post-LDLT, where bleeding occurred in 2/13 cases, prompting endovascular embolization in one patient & laparotomy in the other. Finally, it is worth pointing out that in our LDLT experience, with time, we gradually implemented some additional technical precautions, aiming to minimize the potential risks of endovascular therapy as much as possible.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, in most LDLT centres around the world, surgical revascularization is the preferred therapeutic approach for dealing with e-HAT in the very early posttransplant period 'the first 48 hrs post-transplant'; but over the past decade, a few reports have described the use of endovascular procedures for treatment of e-HAT at this early stage [4,5,12,15,[23][24][25][26]. For instance, a recent LDLT report by Choi et al [23] has shown that surgical revascularization was the most commonly employed initial treatment modality in the 7 patients who developed e-HAT in the first postoperative week [4 cases (57.1%)/POD1; n = 4/technical success rate: 100%], whereas endovascular therapy was carried out in the remaining 3 cases (42.9%) [POD1; n = 2/technical success rate: 66.7%], two of whom developed graft failure & underwent re-transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, subgroup analysis stratified by type of LT showed that the pooled estimate prevalence of HAT after LDLT in patients with PA at 13% was higher than that reported in other studies. 40,41 However, given the small number of PA patients having received LDLT (n = 18), it is still difficult to conclude that PA patients are more likely to develop HAT posttransplant, but this finding suggests that transplant clinicians should be alert to the potentially high risk of developing HAT in PA patients receiving LDLT. Taken together, LT for treating PA showed an adequate safety profile.…”
Section: Discussionmentioning
confidence: 99%